1980
DOI: 10.1159/000287423
|View full text |Cite
|
Sign up to set email alerts
|

Social Psychotherapy and Course of the Disease

Abstract: This paper is designed to introduce anew therapeutic approach into the treatment of cancer patients and to give some first results of our work. The basic idea is that the development of cancer depends to a great extent on a patient’s social environment and the interrelation between environment and patient. A disturbed attitude on the part of the patient towards it and towards himself can influence adversely the development of cancer. The aim of social psychotherapy is to modify such attitudes, i.e. to influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Similar psychosocial treatment has been mounted in cancer patients [250], with one study noting small improvement in sclerosis [249] and another enhanced survival time and lymphocyte breast count in breast cancer patients [251]. Studies examining different type of psychosocial intervention generally found health improvements for behavior therapy, which focuses on altering patterns of thoughts and behavior, but not for psychoanalytic therapy, which focused on developing insight into unconscious motivations [251, 252].…”
Section: Next Steps In Translational and Applied Researchmentioning
confidence: 99%
“…Similar psychosocial treatment has been mounted in cancer patients [250], with one study noting small improvement in sclerosis [249] and another enhanced survival time and lymphocyte breast count in breast cancer patients [251]. Studies examining different type of psychosocial intervention generally found health improvements for behavior therapy, which focuses on altering patterns of thoughts and behavior, but not for psychoanalytic therapy, which focused on developing insight into unconscious motivations [251, 252].…”
Section: Next Steps In Translational and Applied Researchmentioning
confidence: 99%
“…It is simply not correct that Spiegel's study in 1989 was the first investigation of the effects of psychosocial interventions on cancer survival. Several other studies had done this previously 1 2 3 4 5 but Spiegel's study was of higher methodological quality than the earlier ones.…”
Section: Author's Replymentioning
confidence: 92%
“…Grossarth-Maticek had described treating 50 people who were considered at risk of cancer based on his earlier psychosomatic hypotheses. He appears to have used an integrated model of insight-oriented psychoanalytic and supportive psychotherapy (Grossarth-Maticek, 1980b; Grossarth-Maticek et al, 1982). For some reason, until he began working with Eysenck, he never mentioned that in 1972 he had started a clinical trial on 50 closely matched pairs of cancer-prone subjects and 46 pairs with the heart-disease-prone personality drawn from the ‘high psychosomatic risk’ observational cohort (Grossarth-Maticek and Eysenck, 1991).…”
Section: Research On Aetiology and Preventionmentioning
confidence: 99%